L'Anconitana = The woman from Ancona - Ruzzante, 1502?-1542 (Biblioteca italiana., 1994)
"In Italy Angelo Beolco, called Ruzante, is recognized as the most original of the Italian Renaissance dramatists. However, his plays are hardly known in English, mainly because few translators have been able to take on the Pavano dialect Ruzante employed for the character he played. With Nancy Dersofi's vigorous and faithful translation of L'Anconitana, presented opposite the authoritative version of the Italian text, Ruzante's most successful and thoroughly original play is now available to English-speaking audiences for the first time." "Born in Padua just before 1500, Ruzante practiced the genre of comedy in the vernacular, which originated in the humanist revival of ancient drama, and anticipated the professional actors' theater of the commedia dell'arte. To distinguish his character types Ruzante used various dialects. Italian, Venetian, and Pavano appear in L'Anconitana. Modern interest is now focusing again on dialect literature, which reflects the contemporary popular culture and explores the realities of peasant life. Book jacket."--BOOK JACKET.